2003
DOI: 10.1046/j.1528-1157.2003.08603.x
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Patterns of Cerebral Glucose Metabolism, Perfusion, and Magnetic Field in Mesial Temporal Lobe Epilepsy

Abstract: MEG-ECD was distributed in varied ways with the disorder and uncoupling of glucose metabolism and perfusion in the temporal lobe. These results may help resolve the clinical controversy over the possibility that the cortical irritative area generating the interictal epileptic discharge is distinct from the ictal-onset area, and also may have some functional implications in identifying different brain compartments in the generation of metabolic signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The spatial pattern of this network was similar to that of the temporal epileptic network reported in other studies using different imaging modalities [Bernhardt et al, 2008;Blumenfeld et al, 2004;Spencer, 2002;Tae et al, 2005]. Although a general consensus has been reached that the hippocampus is the key of the epileptogenic focus, increasing evidence has shown that widespread brain structures, including the bilateral mesial temporal structures [Bernhardt et al, 2008;Seidenberg et al, 2005;Spencer, 2002], neocortices such as the lateral temporal [Blumenfeld et al, 2004;Tae et al, 2005] and parietal lobes [Englot et al, 2008;Nelissen et al, 2006;Tae et al, 2005], subcortical structures such as the thalamus [Labate et al, 2008;Schwarcz et al, 2002;Yune et al, 1998], basal ganglia and pontine nuclei [Bouilleret et al, 2005] etc., compose a reciprocal mesial temporal epileptic network contributing to the process of mTLE [Blumenfeld et al, 2004;Sakamoto et al, 2003;Spencer, 2002]. The largely overlapped results might implicate that the widespread increased ALFF is underpinned by the mesial temporal epileptic network proposed by Spencer [2002].…”
Section: Regions Showing Increased Alff and The Temporal Epileptic Nementioning
confidence: 90%
“…The spatial pattern of this network was similar to that of the temporal epileptic network reported in other studies using different imaging modalities [Bernhardt et al, 2008;Blumenfeld et al, 2004;Spencer, 2002;Tae et al, 2005]. Although a general consensus has been reached that the hippocampus is the key of the epileptogenic focus, increasing evidence has shown that widespread brain structures, including the bilateral mesial temporal structures [Bernhardt et al, 2008;Seidenberg et al, 2005;Spencer, 2002], neocortices such as the lateral temporal [Blumenfeld et al, 2004;Tae et al, 2005] and parietal lobes [Englot et al, 2008;Nelissen et al, 2006;Tae et al, 2005], subcortical structures such as the thalamus [Labate et al, 2008;Schwarcz et al, 2002;Yune et al, 1998], basal ganglia and pontine nuclei [Bouilleret et al, 2005] etc., compose a reciprocal mesial temporal epileptic network contributing to the process of mTLE [Blumenfeld et al, 2004;Sakamoto et al, 2003;Spencer, 2002]. The largely overlapped results might implicate that the widespread increased ALFF is underpinned by the mesial temporal epileptic network proposed by Spencer [2002].…”
Section: Regions Showing Increased Alff and The Temporal Epileptic Nementioning
confidence: 90%
“…The aim of our study was to determine the changes and sensitivity of interictal EEG in demonstrating the pathological abnormality and evaluate the presence of paroxysm of epileptiform discharges with clinically suspected seizure events. Other technologies currently used for epileptic focus lateralization, such as magneto electroencephalography (MEG) and functional magnetic resonance imaging ( f MRI) also depend largely on analysis of interictal spikes (Sakamoto et al 2003; Al-Asmi et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…The promising applications of a wide variety of functional neuroimaging options for assessing epileptic foci as well as ictal and interictal perfusion patterns further emphasizes the need to carefully define pathways linking medial temporal lobe structures with motor cortex. For example, brain activation patterns accompanying seizures are currently interpreted utilizing the existing body of anatomical knowledge to classify seizures, localize and lateralize epileptogenic foci, assess seizure propagation pathways, guide presurgical strategies, and predict postoperative seizure outcomes following surgical intervention (Engel et al,1983; Stefan et al,1990; Rowe et al,1991; Marks et al,1992; Theodore et al,1992; Kuzniecky et al,1993; Radtke et al,1993; Ho et al,1997; Laich et al,1997; Duncan,2000; Rosenow and Lûders,2001; Wichert‐Ana et al,2001; Antel et al,2002; Sakamoto et al,2003; Joo et al,2005; Tae et al,2005). Therefore, accurate characterization of medial temporal projection patterns remains a priority for developing palliative and beneficial epileptic surgical strategies.…”
mentioning
confidence: 99%